DEVELOPMENT OF NATURAL DISASTER MITIGATION LITERACY TEACHING MATERIALS WITH THE HELP OF BOOK CREATOR FOR JUNIOR HIGH SCHOOL STUDENTS - Emasta Evayanti Simanjuntak; Vismaia S. Damaianti; Welly Nores Kartadireja; Nurfidah Nurfidah (Universitas Negeri Makassar, 2024)
This research aims to develop teaching materials for natural disaster mitigation literacy with the help of book creators for junior high school students. The method used is R&D with a 4D model (define, design, develop, disseminate). The population of this study is students of SMP Pasundan 3 Bandung with a sample of class VIII A of 29 people. The data analysis techniques used are qualitative descriptive and quantitative descriptive. In the effectiveness test of teaching materials, the data analysis used was a paired sample t-test. The results of the study show that based on the analysis of the need for the availability of teaching materials, natural disaster mitigation literacy is still limited and 90% of students do not know about natural disaster mitigation. At the design stage, natural disaster mitigation media and content are designed to be attractive and easy to understand by combining images and videos in each chapter. At the development stage, the validation of material and media experts was 94.17% and 86.90% which were in the valid category. The effectiveness test showed an increase in student understanding to 72.07 after the posttest with a paired test until a t test of p= 0.000 < 0.05. It can be concluded that innovative digital teaching materials are important in improving students' preparedness for natural disasters.